2012
DOI: 10.1152/physiolgenomics.00128.2011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional implications of ultradian glucocorticoid secretion in homeostasis and in the acute stress response

Abstract: Glucocorticoids exert significant downstream effects, including the regulation of many inflammatory genes. The HPA axis functions such that glucocorticoids are released in a pulsatile manner, producing ultradian rhythms in plasma glucocorticoid levels. It is becoming increasingly evident that this ultradian pulsatility is important in maintaining proper homeostatic regulation and responsiveness to stress. This is particularly interesting from a clinical perspective given that pathological dysfunctions of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Compromised GC diurnal variation has been associated with a reduced ability to respond to acute stressors with rapid GC release [37]. This may be of particular importance in IC/BPS, where symptom flares are often preceded by acute psychosocial stress, and these findings suggest one potential process by which this may occur [35].…”
Section: Discussionmentioning
confidence: 99%
“…Compromised GC diurnal variation has been associated with a reduced ability to respond to acute stressors with rapid GC release [37]. This may be of particular importance in IC/BPS, where symptom flares are often preceded by acute psychosocial stress, and these findings suggest one potential process by which this may occur [35].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the circadian diurnal rhythm in corticosterone levels is necessary for antidepressants to increase adult neurogenesis in rats and potentially to regulate the baseline levels of adult neurogenesis 55 . Whether acute or chronic stress influences these rhythms, and the related glucocorticoid receptor-mediated gene transcription, is not well understood, but it has been proposed that ultradian rhythms have a role in the normal, acute stress response and in its disruption during chronic stress [56][57][58] . The potential importance of these factors in the mechanism by which stress induces changes in neurogenesis remains a pressing question.…”
Section: Glucocorticoid Signalling Mechanismsmentioning
confidence: 99%
“…Though popular speculation has been that oscillations in glucocorticoid production stem from a hypothalamic pulse generator, Walker, Terry [19] found that constant infusion of CRH was still able to generate glucocorticoid oscillation indicating a sub-hypothalamic regulation of the ultradian secretion pattern. More recently, Scheff, Calvano [20] observed that glucocorticoid response to CRH was dependent on the phase of the oscillation. Perhaps implants can impact systemic cortisol levels by altering the ultradian rhythm but without impacting gene expression of ACTH.…”
Section: Discussionmentioning
confidence: 97%